Divergent effects of Porcupine and Wntless on WNT1 trafficking, secretion, and signaling - Galli, Lisa M. (Exp Cell Res, 2016)
Loss-of-function studies have identified Porcupine (PORCN) and Wntless (WLS) as essential mediators of Wnt secretion and signaling. Whereas PORCN is thought to palmitoylate Wnt proteins, WLS is believed to transport palmitoylated Wnt proteins to the cell surface. However, little is known about how these two proteins cooperate to regulate Wnt palmitoylation, trafficking, secretion, and signaling. We first investigated possible interactions between PORCN, WLS, and WNT1, by carrying out co-immunoprecipitation studies. These studies demonstrate the existence of a complex containing PORCN and WLS. They further show that PORCN and WLS compete for binding to WNT1. Then, we used gain-of-function studies to investigate the cooperation between PORCN and WLS as well as possible biochemical interactions between PORCN, WLS, and WNT1. Consistent with the proposed roles for PORCN and WLS, we show that overexpression of PORCN promotes palmitoylation of WNT1 while overexpression of WLS does not. Overexpression of PORCN enhances the ability of WLS to promote WNT1 trafficking to the cell surface as well as secretion, but decreases the ability of WLS to activate WNT1 signaling in target cell. These observations suggest that the levels of WNT1 on the cell surface and in the media are not the sole determinants of the activation of Wnt signaling in target cells.